Forced Vibrations of an Elastic Triangular Plate Supported Around its Perimeter by a Unilateral Support Via the Chebyshev Polynomial Expansion - Celep, Zekai; Özcan, Zeki (Taylor & Francis, 2024)
The present study introduces static and dynamic analysis of an elastic triangular plate on unilateral edge supports, including forced vibrations due to loading and unloading excitation. The plate is assumed to be subjected to a uniformly distributed load and an eccentrically applied concentrated load. Furthermore, the loads are assumed to display dynamic variations. The governing equation of the problem is derived by considering the static and the dynamic responses of the plate by including inertia forces. The analytical solution is conducted by employing a series of Chebyshev polynomials for the admissible displacement functions and using Lagrange’s equations of motion. Having found the governing equation of the problem, an approximate numerical solution is accomplished using an iterative process due to the non-linear properties of the unilateral edge supports. The static behavior of the plate under a concentrated load is investigated in detail numerically by considering a wide range of parameters of the plate geometry and the stiffness of the support. In deriving the governing equation of the problem and in the numerical solution, special care is taken to use nondimensional parameters. This approach ensures that the analysis and conclusions remain valid across a wide range of parameter values. Dynamic treatment of the problem is carried out in the time domain by assuming a stepwise time variation of the concentrated load and by employing the constant acceleration procedure in the numerical solution of the system of governing differential equations derived from the equation of motion. Time variations of the displacements, the contact points, and the reactions of the plate’s support are presented in figures for various values of the parameters of the plate, as well as those of the supports, particularly focusing on the non-linearity of the problem due to the plate liftoff from the unilateral support. The effects of the parameters and the loading are investigated in detail. The results reveal that the unilateral property of the support stiffness significantly affects the static and dynamic behavior of the triangular plate. The analysis can be extended easily to cover a general type of loading as well. The main issues addressed in this study include: the analysis of a triangular plate with unilateral perimeter support that does not resist tensile forces; the use of Chebyshev polynomials as admissible functions in both directions; the consideration of static and dynamic loads; the determination of lifting areas of the support in both cases and the assessment of the global vertical force balance in the plate, including inertia forces in the dynamic case.
Keywords: Elastic Triangular Plate; Forced Vibrations; Static and Dynamic Response; Unilateral Support